Analisis Strategi SEO dalam Pengelolaan Konten WordPress: Kasus Impactlabs Indonesia - Indri Theresa Sitohang; Dadan Abdul Aziz Mubarok (MAMEN: Jurnal Manajemen, 2025)
This study aims to evaluate the effectiveness of Search Engine Optimization (SEO)-based marketing content optimization strategies through the WordPress platform at Impactlabs Indonesia, a technology startup company engaged in the Internet of Things (IoT) and sustainability. Despite having implemented digital marketing since 2021, Impactlabs' website performance has not shown optimal results in terms of traffic, visibility, and user engagement. Using a descriptive qualitative approach and case study, data was collected through interviews, observations, as well as internal documentation and digital metrics analysis. On-page SEO strategies were implemented with a focus on keyword research, content structure optimization, and utilization of Yoast SEO plugin on WordPress. The results showed a significant increase in the number of impressions, click-through rate (CTR), keyword ranking, and visitor engagement. These findings reinforce the role of SEO as part of a consumer-oriented and data-driven digital marketing management strategy. WordPress-based optimization is proven to be able to support increased marketing effectiveness, brand visibility, and overall company digital performance